Parental ethnic identity and educational attainment of second-generation immigrants - Simone Schüller (Institute for the Study of Labor (IZA), 2011)
A lack of cultural integration is often blamed for hindering immigrant families' economic progression. This paper is a first attempt to explore whether immigrant parents' ethnic identity affects the next generation's human capital accumulation in the host country. Empirical results based on data from the German Socio-Economic Panel (GSOEP) indicate that maternal majority as well as paternal minority identity are positively related to the educational attainment of second-generation youth - even controlling for differences in ethnicity, family background and years-since-migration. Additional tests show that the effect of maternal majority identity can be explained by mothers' German language proficiency, while the beneficial effect of fathers' minority identity is not related to language skills and thus likely to stem from paternal minority identity per se.
urn:nbn:de:101:1-2012010913752
Keywords: I21; J15; J16; 330; ethnic identity; second-generation immigrants; education; Migranten; Kulturelle Identität; Bildungsverhalten; Bildungsniveau; Generationenbeziehungen; Schätzung; Deutschland